2003
DOI: 10.1103/physreve.67.036609
|View full text |Cite
|
Sign up to set email alerts
|

Collision of one-dimensional nonlinear chains

Abstract: We investigate one-dimensional collisions of unharmonic chains and a rigid wall. We find that the coefficient of restitution (COR) is strongly dependent on the velocity of colliding chains and has a minimum value at a certain velocity. The relationship between COR and collision velocity is derived for low-velocity collisions using perturbation methods. We found that the velocity dependence is characterized by the exponent of the lowest unharmonic term of interparticle potential energy.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Dynamic buckling and recoil mechanisms of elastic materials have been studied in materials ranging from solids 1 to rubbers 2 and even to non-Newtonian fluids. [3][4][5][6][7][8] When the axial compression of a straight beam exceeds a critical value, a dynamic buckling instability initiates -as noted first by Euler 9 -with a characteristic wavelength. 1,10,11 The threshold character of this phenomenon may be the first practical example of a critical bifurcation of the solution of a differential equation.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic buckling and recoil mechanisms of elastic materials have been studied in materials ranging from solids 1 to rubbers 2 and even to non-Newtonian fluids. [3][4][5][6][7][8] When the axial compression of a straight beam exceeds a critical value, a dynamic buckling instability initiates -as noted first by Euler 9 -with a characteristic wavelength. 1,10,11 The threshold character of this phenomenon may be the first practical example of a critical bifurcation of the solution of a differential equation.…”
Section: Introductionmentioning
confidence: 99%
“…However the results in [27,Figure 2a] show that with equal masses and equal stiffnesses, then e n ≈ 1. This is extended to N -ball systems (see also [28,29]). One assumption that is made in these studies, and might make the analysed chains behaviour different from an elastic rod impacting axially a wall, is that it is assumed that the first (colliding) ball reverses its velocity instantaneously [29].…”
Section: Mathematical Results On the Existence Of Solutions (Velocitymentioning
confidence: 99%
“…• Pages 165-166: estimations of the CoR for harmonic chains of aligned beads colliding a wall, and taking into account sequences of repeated impacts as well as the vibrational energy trapped in the chain, are given in [28,29].…”
Section: Fig 2 Sweeping Process With Frictionmentioning
confidence: 99%
“…This "loss" approaches zero when the length of chain increases. Nagahiro and Hayakawa [21] further indicated that COR would be velocity dependent if the springs are nonlinear.…”
Section: Introductionmentioning
confidence: 99%